Relationship-centred care in health: A 20-year scoping review - Sophie Soklaridis; Paula Ravitz; Gili Adler Nevo; Susan Lieff (The Beryl Institute, 2016)
Relationship-centred care (RCC) is a framework for conceptualizing health care which recognizes that the nature and quality of relationships in health care influence the process and outcomes of health care. Our goal was to undertake a scoping review of the peer-reviewed and grey literature on RCC in health. Using Arksey and O'Malley's scoping review methodology we identified literature about RCC in teaching, learning and clinical practice. Electronic databases were searched, and targeted searches were also conducted for grey literature to capture unpublished material. Subsequently, data abstraction tools were used with eligible studies for analysis. Sixty-nine publications originated mainly from the United States and the United Kingdom by authors from various academic disciplines, of which medicine and nursing were dominant. Thematic analysis revealed that the most commonly cited definition of RCC emerged from the Pew-Fetzer report and focused on the central role of relationships between practitioners and their patients, the community and other practitioners in providing quality care and improving outcomes. The concept of RCC was found to be influenced by theories of sociology, social psychology and psychiatry. The practice of RCC was demonstrated through organizational environments that model RCC, practice settings that focus on the patient or family in care planning, and health professional education that is based on RCC principles. RCC is important to: humanize health care and improve patient care. Our review identified three sub-categories that could add to the relational dimension of the practitioner-organization: practitioner-education, practitioner-profession, and practitioner-practice. Recommendations for future research include: outcome and process studies of health professions education and health care that focuses on RCC. The RCC approach provides a paradigm to move beyond the patient-centred care model by focusing on the central role of all relationships in the delivery and outcomes of care.